Total Saponin of Dioscorea collettii Attenuates MSU Crystal-Induced Inflammation by Inhibiting the Activation of the TLR4/NF-κB Signaling Pathway. (20th October 2021) - Guoying, Li; Li, Li; Siyue, Yang; Lei, Lv; Guangliang, Chen
Abstract : Background . Rhizomes from Dioscorea collettii are extensively used in traditional medicine for the treatment of arthritic diseases, particularly gouty arthritis (GA). This study aims to investigate whether the total saponin of Dioscorea collettii (TSD) can attenuate monosodium urate (MSU) crystal-induced inflammatory effects by suppressing the activation of the TLR4/NF- κ B signaling pathway in vivo and in vitro . Methods . Seventy-two male Wistar rats and THP-1 cells were used in this study. Pathological examination was used to examine the ankle joints of rats. The expression levels of TLR4, NF- κ B, MyD88, and IL-1 β were detected by qRT-PCR, Western blotting, or immunofluorescence. Results . Compared with those in the normal group, the ankle joints of rats in the model group exhibited significant swelling, synovial tissue hyperplasia, inflammatory cell infiltration, and increased expression of IL-1 β protein. The joint swelling degree of rats in the TSD high- and medium-dose groups and the colchicine group was significantly decreased, and the histopathology was obviously improved. TSD and colchicine reduced the levels of IL-1 β and TNF- α in synovial fluid. They also decreased the mRNA expression of TLR4, NF- κ B, and IL-1 β in rat joint synovial tissue and the protein expression of TLR4, MyD88, and NF- κ B. NF- κ B protein expression in both the cytoplasm and nuclei of THP-1 cells showed the opposite trend. Furthermore, immunofluorescence showed that TSD reduced the nuclear translocation of NF- κ Bp65 in the model group. Conclusion . TSD exhibits an anti-inflammatory effect in the MSU-induced inflammation model, and the mechanism may be to reduce the production of cytokines by inhibiting the activation of the TLR4/NF- κ B signaling pathway.